Elevated Middle Cerebral Artery Peak Systolic Velocity in a Nonanemic Fetus with Alpha-Thalassemia Trait - Kent Heyborne (Obstetrics and Gynecology International)
Background. Elevated middle cerebral artery peak systolic velocity (MCA-PSV) has been reported in nonanemic fetuses following fetal transfusion, and has been attributed to a major population of red blood cells (RBCs) with an adult mean corpuscular volume (MCV) in the fetal circulation. Reported here is an analogous case of elevated MCA-PSV with a normal fetal hematocrit and relative fetal microcytosis due to fetal α-thalassemia trait. Case. Ultrasound findings concerning for early hydrops prompted measurement of MCA-PSV, which was elevated. Cordocentesis revealed fetal microcytosis with a normal hematocrit which proved to be due to fetal α-thalassemia trait inherited from the mother. Conclusion. This case provides another example of elevated MCA-PSV with normal hematocrit and microcytosis, here due to fetal α-thalassemia trait. This finding provides support for the observation that MCA-PSV may be influenced by hematological indices other than the fetal hematocrit.